2002
DOI: 10.1055/s-2002-32364
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto Encephalopathy - is it Underdiagnosed in Pediatric Patients?

Abstract: Hashimoto encephalopathy (HE) is associated with Hashimoto thyroiditis. Clinically it presents with variable symptoms like seizures, neuropsychiatric changes or focal neurological deficits. Autoimmune phenomena are hypothesized for the pathogenesis. HE has mainly been described in the adult population. We present two 14-year-old patients who presented with recurrent seizures and mental decline. SPECT and PET scans showed distinctly pathological changes. Both patients were diagnosed with HE and improved dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 11 publications
0
34
0
3
Order By: Relevance
“…11 Regarding brain imaging studies; In a review of 82 patients with HE, brain computed tomography or MRI showed abnormalities in 49% such as cerebral atrophy, focal cortical abnormality, diffuse subcortical abnormality and nonspecific subcortical focal white matter abnormality. 12 The acute confusional state seen in HE is recognized as not related to the thyroid status. Correction or near correction of thyroid function abnormalities is frequently required for the diagnosis of this condition.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…11 Regarding brain imaging studies; In a review of 82 patients with HE, brain computed tomography or MRI showed abnormalities in 49% such as cerebral atrophy, focal cortical abnormality, diffuse subcortical abnormality and nonspecific subcortical focal white matter abnormality. 12 The acute confusional state seen in HE is recognized as not related to the thyroid status. Correction or near correction of thyroid function abnormalities is frequently required for the diagnosis of this condition.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It was repeatedly underlined that, especially in children, several cases of such encephalopathy remained unrecognized for a considerable time (8, 23, 24). However, in several cases, a clear thyroid disorder, mostly presenting as hypofunction, could provide useful streamlining diagnostic guidance in patients with various neuropsychiatric signs.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…2,3 Bij volwassenen wordt het beeld van Hashimoto-encefalopathie sneller herkend dan bij kinderen. 4 Vroege herkenning is echter ook bij kinderen van belang vanwege de meestal gunstige en snelle reactie op corticosteroïden. 5 Met de volgende casus willen we de problematiek bij het stellen van de diagnose Hashimoto-encefalopathie op de kinderleeftijd illustreren.…”
Section: Hal De Vries Of Brouwer Jf Goorhuis G Boccaunclassified